Applications of the experience sampling method: a research agenda for hospitality management. Issue 4 (26th February 2020) - Yu, Yitong; Xu, Shi; Li, Gang; Shi, Da
Abstract : Purpose: This study aims to provide researchers in hospitality management with a comprehensive understanding of the experience sampling method (ESM) and to engage them in the use of ESM in their future research. With this critical discussion of the advantages and challenges of the method, researchers can apply it appropriately to deepen and broaden their research findings. Design/methodology/approach: This study chooses an empirical example in the context of hotel employees' surface acting, tiredness and sleep quality to illustrate the application of ESM. Based on the example, this paper conducts a two-level modeling in Mplus, including a cross-level mediation analysis and mean centering. Findings: This paper demonstrates the applicability and usefulness of ESM for hospitality research and provides a detailed demonstration of how to use the statistical program Mplus to analyze ESM data. With this paper, researchers will be able to consider how to engage ESM in their future studies. Originality/value: To the best of the authors' knowledge, this paper is among the first to provide a hands-on demonstration of ESM to hospitality researchers. The authors call for more research in hospitality management to use ESM to answer complex and pressing research questions.